A confirmatory death case of human rabies in Bangladesh - Chowdhury, Md. Jayed; Hossain, Jakir; Jui, Smarnima Ghosh; Al Hasan, Md. Zahid; Akter, Tabassum; Shill, Lincon Chandra; Hussen, Shakhawat (Recent Research in Science and Technology, 2022)
In the present study clinical profile with specific attention to typical clinical presentation and deficiencies/lacunae in post-exposure prophylactic management as per WHO guidelines in adult rabies patients. An observational analysis was performed on a clinically suspected human rabies case, whose samples were gathered at a rabies diagnostic laboratory at Infectious Disease Hospital, Dhaka (IDH) over the course of three days (20/09/2021 to 23/09/2021). The patient’s clinical and demographic information was acquired. The clinical specimens involved cerebrospinal fluid (CSF), saliva, nuchal skin biopsy and serum collected antemortem, and brain tissue obtained post-mortem. A variety of laboratory tests were used to make the diagnosis. The patient died in hospital 3 days after hospitalization (20 days after the occurrence of animal bite). After referring the patient to the IDH, a lumbar puncture was administered, and PCR tests for rabies were forwarded to the cerebrospinal fluid (CSF) and serum. The serum & CSF have indicated antibodies with rabies. The fluorescence microscopy screening program for rabies was positive in the brainstem, cerebral cortex, cerebellum, and cerebrum. The patient’s samples of saliva (0.5-1 mL) and skin were also sent to PCR for rabies. Diagnostic testing of the patient later confirmed human rabies. Human rabies is a crucial health problem. So, there are required to educate the community and health workers about the value of immediate and adequate post-exposure treatment, to launch an effective control program for rabid dogs, and to make availability of rabies vaccine as well as rabies immunoglobulin (RIG).